2014
DOI: 10.1088/0004-637x/784/2/129
|View full text |Cite
|
Sign up to set email alerts
|

Study of Interstellar Molecular Clouds Using Formaldehyde Absorption Toward Extragalactic Radio Sources

Abstract: We present new Very Large Array 6 cm H 2 CO observations toward four extragalactic radio continuum sources (B0212+735, 3C 111, NRAO 150, BL Lac) to explore the structure of foreground Galactic clouds as revealed by absorption variability. This project adds a new epoch in the monitoring observations of the sources reported by Marscher and collaborators in the mid 1990's. Our new observations confirm the monotonic increase in H 2 CO absorption strength toward NRAO 150. We do not detect significant variability of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…As in the case of 3C111, 69 observed H 2 CO in absorption in the direction of BL Lac. They estimated rough bounds on the density, 10 2 cm −3 ≲ n H ≲ 10 5 cm −3 , on the basis of the H 2 CO absorption properties (see explanation above for 3C111).…”
Section: Localizing Absorption Featuressupporting
confidence: 61%
See 2 more Smart Citations
“…As in the case of 3C111, 69 observed H 2 CO in absorption in the direction of BL Lac. They estimated rough bounds on the density, 10 2 cm −3 ≲ n H ≲ 10 5 cm −3 , on the basis of the H 2 CO absorption properties (see explanation above for 3C111).…”
Section: Localizing Absorption Featuressupporting
confidence: 61%
“…We first attempt to find density estimates from the literature in the direction of our background sources. Araya et al (2014) observed H 2 CO in absorption in the directions of 3C111 and BL Lac. They argued that the excitation temperature of H 2 CO implies an upper limit to the density of n H < 10 5 cm −3 in these directions, while the relatively weak absorption by H 2 CO compared to CO and HCO + suggests that the density probably exceeds n H 10 2 cm −3 .…”
Section: Density Constraintsmentioning
confidence: 93%
See 1 more Smart Citation
“…Specifically, 60″ resolution observations have been reported toward only a handful of late-type stars (Forster et al 1985;Araya et al 2003), regions of low-mass star formation (including prestellar cores; Colgan et al 1986;Zhou et al 1990;Kalenskii et al 2004;Young et al 2004;Araya et al 2006b), and diffuse molecular clouds (Marscher et al 1993;Araya et al 2014), all resulting in no detection of H 2 CO emission.…”
Section: Introductionmentioning
confidence: 99%
“…For the central position this results in T rot ≈130 ± 100 K versus T myXCLASS ≈ 70 K 12 using the rotational diagram and myXCLASS, respectively, 11 In position 2 (southeast) and position 3 (north) the H 2 CO line is also partly seen in absorption. Absorption features of H 2 CO at radio wavelengths were seen as early as 1969 (see Palmer et al 1969) and are still in use as diagnostic tool (see Araya et al 2014). In our case the absorption happens against the radio continuum at the mentioned source positions.…”
Section: H 2 Co Observationsmentioning
confidence: 53%